2010
DOI: 10.1177/0956247809356182
|View full text |Cite
|
Sign up to set email alerts
|

Embedding international migration: the response of Bolivian local governments and NGOs to international migration

Abstract: International migration is an integral part of the lives of many people in the South, and many households add remittances to their income in order to finance the daily costs of living that cannot be met by their traditional source of income. In the literature, a debate has emerged on the impacts of these remittances on development, focusing in particular on the micro level, namely the impact on households. Many studies also contend that national governments should try to redirect the impacts of remittances. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…As part of these processes, local communities, actors, and governments may aim to attract or reject international migrants, either high or low skilled. Similarly, they may try to limit or encourage outmigration, attract remittances, channel investments, or concern themselves with the social problems arising from transnational dynamics (Nijenhuis, ). Against this background, migration scholars advocate a closer account of the interplay of scaling processes and the differential outlook these have across localities in relation to the processes of migration, local incorporation, and transnational network formation (Glick‐Schiller & Çağlar, ).…”
Section: Transformation and Transnationalitymentioning
confidence: 99%
“…As part of these processes, local communities, actors, and governments may aim to attract or reject international migrants, either high or low skilled. Similarly, they may try to limit or encourage outmigration, attract remittances, channel investments, or concern themselves with the social problems arising from transnational dynamics (Nijenhuis, ). Against this background, migration scholars advocate a closer account of the interplay of scaling processes and the differential outlook these have across localities in relation to the processes of migration, local incorporation, and transnational network formation (Glick‐Schiller & Çağlar, ).…”
Section: Transformation and Transnationalitymentioning
confidence: 99%
“…The last mechanism to be discussed, discursive standardisation , leads us back to the first question about the relevance of global trends. For example, in a study on local (development) policies in selected regions and towns, in Bolivia Nijenhuis () found that cross‐border migration is an issue in these cases and that remittances and other forms of exchange are discussed and evaluated carefully. However, there were no active efforts on the part of the respective government authorities to actively forge ties with their ‘diaspora’ abroad.…”
Section: Consequences Of Scale Shift For Power Asymmetries and Socialmentioning
confidence: 99%
“…The Burkinabé (inhabitants of Burkina Faso) are also migrating increasingly to Italy. The Bolivians, who were for a long time oriented towards Argentina in looking for work, migrated at the start of the new millennium in large numbers to Spain [62]. There is also increasing intercontinental migration, e.g., of Chinese who travel to Europe or the US via Kenya.…”
Section: International Migration: a Global Picturementioning
confidence: 99%
“…Conflicts are relatively quickly translated into inter-state problems; problems of discrimination and/or xenophobia (which also arise in the north), however, remain relatively invisible there, because the media pay attention mainly to tensions in the northern countries. Many Bolivians and Paraguayans have also returned to their own country from Argentina as a result of the economic crisis [62].…”
Section: Migration and Development: Different Flows Different Opportmentioning
confidence: 99%